2013
DOI: 10.1345/aph.1r707
|View full text |Cite
|
Sign up to set email alerts
|

Subtherapeutic Linezolid Concentrations in a Patient with Morbid Obesity and Methicillin-Resistant Staphylococcus aureus Pneumonia: Case Report and Review of the Literature

Abstract: To our knowledge, this is the first report of subtherapeutic linezolid concentrations correlated with decreased clinical effectiveness when during treatment of MRSA pneumonia in a patient with morbid obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, in obese patients, observed serum levels have been lower than in the nonobese population, with one case report of a patient with a body mass index (BMI) of 37 describing clinical failure because of reduced serum concentration trough levels below the MIC 90 (MIC for 90% of the isolates) [69]. This suggests that there may be a need for increasing the dose in morbidly obese patients or in those >50% of their calculated ideal body weight [69][70][71].…”
Section: Linezolidmentioning
confidence: 99%
“…However, in obese patients, observed serum levels have been lower than in the nonobese population, with one case report of a patient with a body mass index (BMI) of 37 describing clinical failure because of reduced serum concentration trough levels below the MIC 90 (MIC for 90% of the isolates) [69]. This suggests that there may be a need for increasing the dose in morbidly obese patients or in those >50% of their calculated ideal body weight [69][70][71].…”
Section: Linezolidmentioning
confidence: 99%
“…There is limited evidence to guide dosing in obesity in the critically ill; however, published studies and case reports suggest higher doses of lipophilic antibacterials are required in this setting. 15,16 Reduced bacterial susceptibility For organisms with high MIC values, application of PK/PD models, increasing the total daily dose of the antibacterial with TDM (where applicable) should be considered.…”
Section: Loading Dose (Ld)mentioning
confidence: 99%
“…Limited data on linezolid dosing in the morbidly obese population show lower serum drug concentrations than those in nonobese patients with potential treatment failure (Muzevich et al 2013 ). Two studies have shown increased clearance of linezolid and reduced serum concentration compared to population pharmacokinetic parameters, with trough levels below MIC 90 (Tsuji et al 2012a ;Stein et al 2005 ).…”
Section: Obese Patientsmentioning
confidence: 99%